RELATED RIGHTS: CONCEPT, FEAUTURES AND LEGAL PROTECTION UNDER THE LAWS OF UZBEKISTAN AND EUROPIAN COUNTRIES - Murodiljon O. Orifjonov; Akhrorkhon A. Nabiraev (Scholars Digest Publishing, 2023)
In the modern world, every person daily encounters the results of intellectual or creative activity, whether it is, for example, reading a famous book or listening to a popular music during a walk. Both books and music are the result of human activity, have intangible value, and, in other words, referred as the institution of copyright and related rights. In this article, we will analyze in detail the concept of related rights, as well as their characteristic features and ways of their protection.  For this purpose, we will refer to the legislation and experience of both the Republic of Uzbekistan and European countries – Germany, France, and Italy, applying analytical and comparative methods. In conclusion, a number of recommendations will be given to improve Uzbek legislation.
Keywords: intellectual right, copyright, related rights, performer, producers of phonograms and broadcasting, moral defense.